2011
DOI: 10.1074/jbc.m110.173252
|View full text |Cite
|
Sign up to set email alerts
|

Insulin-degrading Enzyme Modulates the Natriuretic Peptide-mediated Signaling Response

Abstract: The natriuretic peptides (NPs), 2 mainly atrial (ANP), Btype (BNP), and C-type natriuretic peptides (CNP), play key roles in many cardiovascular functions (1). Their diuretic, natriuretic, and vasodilatory properties have been developed as therapeutic strategies for human cardiovascular diseases (2). The actions of NPs are mediated through binding and signal transduction of three natriuretic peptide receptors (NPR). NPR-A and NPR-B have guanylyl cyclase activity that raises intracellular cGMP levels. Effects o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
59
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(62 citation statements)
references
References 31 publications
(42 reference statements)
2
59
0
1
Order By: Relevance
“…This agrees with biochemical data that IDE R767A exists mostly as a monomer, but some dimers can still form (Fig. 4C) (10). IDE S132C/E817C introduces a disulfide bond to lock IDE D1 and D4 together, which only becomes active under reducing conditions (7).…”
Section: Roles Of Ide Swinging Door In Substrate Recognition and Rate Ofsupporting
confidence: 79%
See 1 more Smart Citation
“…This agrees with biochemical data that IDE R767A exists mostly as a monomer, but some dimers can still form (Fig. 4C) (10). IDE S132C/E817C introduces a disulfide bond to lock IDE D1 and D4 together, which only becomes active under reducing conditions (7).…”
Section: Roles Of Ide Swinging Door In Substrate Recognition and Rate Ofsupporting
confidence: 79%
“…S1) (3, 7). IDE uses the size, shape, and charge distribution of its chamber (∼13,000 Å 3 ) to selectively engulf structurally diverse peptides, such as insulin, Aβ, tumor growth factor-α, macrophage inflammatory protein-1α (MIP-1α), natriuretic peptides, and amylin (7)(8)(9)(10)(11). IDE substrates are presumably unraveled inside the catalytic chamber and then stochastically cleaved in regions that have a high propensity to convert into a β-strand for the formation of intermolecular cross-β sheets, the fundamental structural element of amyloid fibrils (7)(8)(9).…”
mentioning
confidence: 99%
“…The variety of such fragments is believed to be the result of proteolysis by dipeptidyl peptidase IV (DPP IV), which forms BNP 3-32 and neprilysin (NEP), which forms BNP 5-32. BNP can also be proteolyzed by insulindegrading enzyme (IDE), but not by NEP and IDE implying that another enzyme is involved in cleavage (25 ). BNP 4 -32 may be the result of corin activity (21 ).…”
Section: Degradation Fragments Of Bnp In Circulationmentioning
confidence: 99%
“…62 Ralat et al reported that IDE rapidly cleaves ANP, so inhibition of IDE expression may enhance the action of GC-A by prolonging the half-life of ANP. 63 Inhibition of IDE in CVD has not investigated yet, but IDE inhibition may be a good therapeutic for type II diabetes and Alzheimer's disease, as has been reported. 64, 65 For example, Maianti et al performed a chemical and biochemical survey of a DNAtemplate library and found an optimal small-molecule inhibitor, 6bk IDE inhibitor.…”
Section: Phase I Clinical Trial For Htmentioning
confidence: 99%